Conservative Management of Post-Operative Cerebrospinal Fluid Leak following Skull Base Surgery: A Pilot Study - Aria M. Jamshidi; Ashish Shah; Daniel G. Eichberg; Ricardo J. Komotar; Michael Ivan (Brain Sciences, 2022)
Background/aims: Iatrogenic CSF leaks after endoscopic endonasal transsphenoidal surgery remain a challenging entity to manage, typically treated with CSF diversion via lumbar drainage. Objective: To assess the safety and efficacy of high-volume lumbar puncture (LP) and acetazolamide therapy to manage iatrogenic CSF leaks. Methods: We performed a prospective pilot study of four patients who developed iatrogenic postoperative CSF leaks after transsphenoidal surgery and analyzed their response to treatment with concomitant high-volume lumbar puncture followed by acetazolamide therapy for 10 days. Data collected included demographics, intra-operative findings, including methodology of skull base repair and type of CSF leak, time to presentation with CSF leak, complications associated with high-volume LP and acetazolamide treatment, and length of follow-up. Results: Mean patient age was 44.28 years, with an average BMI of 27.4. Mean time from surgery to onset of CSF leak was 7.71 days. All four patients had resolution of their CSF leak at two- and four-week follow-up. Mean overall follow-up time was 179 days, with a 100% CSF leak cure rate at the last clinic visit. No patient suffered perioperative complications or complications secondary to treatment. Conclusion: Although our pilot case series is small, we demonstrate that a high-volume LP, followed by acetazolamide therapy for 10 days, can be considered in the management of post-operative CSF leaks.